Photothermal effects on protein adsorption dynamics of PEGylated gold nanorods. (June 2019) - Polo, Ester; Araban, Vida; Pelaz, Beatriz; Alvarez, Aitor; Taboada, Pablo; Mahmoudi, Morteza; del Pino, Pablo
Graphical abstract: Highlights: PEGylation of GNRs reduces the protein adsorption independently of their net charge. Surface charged PEGylations on GNRs affects the dynamics of protein corona formation. Influence of the photothermal heating in the interplay of PEGylated GNR, with proteins and cells. PEGylation and BSA corona formation prevents GNRs's uptake by cells. Abstract: The effect of thermoplasmonic heating on the dynamics of the protein corona around polyethylene glycol (PEG) coated gold nanorods (GNRs) is reported. GNRs were surface-modified with densely packed shells composed of thiolated PEGs bearing carboxyl and/or amine end-terminal groups, which led to negatively, positively or neutral charged GNRs. The three types of PEGylated GNRs, although with subtle differences among them, present weak interactions (binding dissociation constants in the μM range) with the model protein bovine serum albumin (BSA), as determined by different methods including gel electrophoresis, laser Doppler anemometry and isothermal titration calorimetry (ITC). In general, plasmonic photothermal heating significantly changed the composition of the protein corona around GRNs, particularly, on the positively charged ones. Moreover, a pre-formed BSA corona on the PEGylated GNRs further decreased their already reduced uptake by cells. However, photothermal treatment of BSA-coated GNRs only produced a significant decreased internalization in the case of non-PEGylated control samples. Overall, our results indicate that differently surface charged PEGylations on GNRs affects the dynamics of protein corona formation, which is particularly relevant after photothermal treatment. Such effects are nonetheless non-significant concerning cellular uptake.